Natural product nobiletin-loaded Pickering emulsion stabilized by bovine serum albumin/carboxymethyl inulin complexes: preparation and digestive characteristics - Huang, Guiying; Zhang, Man; Feng, Konglong; Xiao, Jie; Huang, Qingrong; Ho, Chi-Tang; Liu, Jun (Frontiers in Pharmacology, 2024)
To expand the application of nobiletin in semi-solid functional foods, bovine serum albumin/ carboxymethyl inulin (CMI) complexes-stabilized Pickering emulsion (oil = 60%, v/v) was fabricated, as well as the swallowing index and bioavailability of the nobiletin-loaded Pickering emulsion had been evaluated. Confocal laser scanning microscope (CLSM) and cryo-scanning electron microscopy (cryo-SEM) images exhibited that bovine serum albumin/ carboxymethyl inulin complexes attached to the oil-water interface. Nobiletin-loaded BCPE exhibited a viscoelastic and shear-thinning behavior. Fork drip test results suggested that the textural value of unloaded and nobiletin-loaded emulsions was IDDSI Level 4, which could be swallow directly without chewing. The in vitro lipolysis model suggested that nobiletin had a faster digestive profile and a higher bioaccessibility in the BCPE than in the oil suspension. The in vivo rat model revealed that the oral bioavailability of nobiletin was increased by 2.07 folds in BCPE than that in unformulated oil. Moreover, BCPE led to a higher plasma concentration of the major demethylated metabolite of nobiletin (4´-demethylnobiletin) than the unformulated oil. Accordingly, BCPE enhanced the oral bioavailability of nobiletin via improving bioaccessibility, absorption, and biotransformation.